An Optimized Sponge for microRNA miR-9 Affects Spinal Motor Neuron Development in vivo - Otaegi, Gaizka; Pollock, Andrew; Sun, Tao (Frontiers in Neuroscience, 2012)
The specification of motor neuron (MN) subtypes and columnar organization in developing spinal cord is controlled by multiple transcription factors. FoxP1 drives specification of lateral motor neuron (LMN) subtypes, and we demonstrated in our previous work that FoxP1 expression levels are regulated by the microRNA miR-9. Here we show that ectopic FoxP1 expression can rescue altered LMN development caused by miR-9 over-expression, demonstrating that FoxP1 is the critical interaction partner for miR-9 in LMN development. Moreover, we have optimized this technique, called a miRNA sponge, to permit easy discovery of the role of individual miRNA in vivo using a loss-of-function approach. We here show that narrow spacing between binding sites and inclusion of a coding gene, and optimizing the number of miRNA binding sites can significantly increase the blocking ability of a sponge. We go on to show that a miR-9 sponge reduces detectable miR-9 in the ventral horn, preventing miR-9 silencing of FoxP1 in vivo, and in turn modifies MN subtypes in the spinal cord. Our designs for optimized sponges provide a knockdown tool that is ready to be used to study the function of miRNA in vivo, and in particular for generating transgenic animal models.